Measuring Child Deprivation and Opportunity in Australia: Applying the Nest framework to develop a measure of deprivation and opportunity for children using the Longitudinal Study of Australian Children - Sollis, Kate (Australian Research Alliance for Children and Youth, 2019)
This report develops a measure of deprivation to assess the wellbeing of children and young people using the Longitudinal Study of Australian Children (LSAC) as a representative sample. The measure utilised the UNICEF MODA methodology, and was based on ARACY’s Nest framework which specifies that there are six dimensions of a child’s life where they need to be thriving to be said to have high wellbeing; that they are loved and safe, have material basics, are healthy, are learning, are participating in society and have a positive sense of identity and culture. Developing such a tool allows us to uncover the major issues affecting the wellbeing of children in Australia and to assess how children living in difficult circumstances may suffer from greater levels of deprivation in wellbeing areas. This helps to drive policy interventions to improve the lives of children in Australia. A deprivation index was produced using waves 4, 5 and 6 of the Baby cohort in LSAC, corresponding to children aged 6-7 in 2010, 8-9 in 2012 and 10-11 in 2014. The index is comprised of five dimensions of wellbeing, aligning with the Nest framework. The Nest dimension of Positive Sense of Identity and Culture was not used due to its close relationship with the other Nest dimensions. Indicators were selected based on the Nest consultations conducted in 2012, which asked around 3,700 children and young people what it means to them to live a good life. Cut-off points for ‘deprivation’ were then empirically derived for each indicator at each wave. A child was considered to be deprived in a dimension if they were deprived in any indicator within that dimension. A measure of multi-dimensional deprivation was developed, defined as being deprived in three or more dimensions, as well as deep deprivation which is defined as being deprived in two or more indicators within a dimension. The analysis found that while children in Australia are generally faring well, with around one quarter of children having high wellbeing in all Nest dimensions, deprivation still exists in the country, with around one-fifth of children being multi-dimensionally deprived, and up to one-quarter experiencing a deep deprivation in at least one dimension. Children facing more difficult life circumstances are significantly more likely to have deprivations across all areas of their wellbeing, with children in three population groups - children with disability, children living in monetary poverty, and children in jobless families – compared with their peers. The results show that all groups experienced higher levels of deprivation across all wellbeing dimensions. Children in jobless families, in particular, suffered from a greater number of deprivations. In light of these findings, we present six policy recommendations for which the evidence has shown to improve the issues identified in the report. These are: 1. Increase assistance to low-income families 2. Introduce regulation to reduce the amount of unhealthy food marketing reaching children 3. Introduce evidence-based anti-bullying programs in all Australian schools 4. Prioritise preventative and early intervention mental health programs 5. Establish a more inclusive education system with adequate resourcing 6. Collect better data on children and young people in Australia
Keywords: Health -- Wellbeing; Finance -- Poverty and disadvantage; Children; Health and wellbeing; Income, wealth and finances; Children; Finance; Health; Poverty and disadvantage; Wellbeing; Health and wellbeing; Income, wealth and finance